Jackhammer oesophagus in a case of linitis plastica - Chaudhry, Naueen Akbar (BMJ Case Rep, 2016)
A 52-year-old Caucasian woman presented with progressive nausea and vomiting, weight loss, and burning epigastric and chest pain. Initial oesophagogastroduodenoscopy (OGD) with biopsies demonstrated gastritis in absence of Helicobacter pylori. A gastric emptying study, CT scan with pancreatic protocol and a colonoscopy revealed no concerning findings. Calcium channel blockers and proton pump inhibitors offered little improvement. A high-resolution oesophageal impedance manometry was performed, which was significant for jackhammer oesophagus with maximum distal contractile index 11 052 mm Hg-s-cm. Another OGD was carried out for Botox injection to oesophagogastric junction. Repeat gastric biopsies reported gastric adenocarcinoma, further diagnosed as stage 4 linitis plastica with metastatic peritoneal carcinomatosis. To the best of our knowledge, this is the only case of linitis plastica associated with jackhammer oesophagus.